Imagens de herbários do século XVI como formas de registro e comunicação de conhecimentos: O herbário de William Turner (c.1510 - 1568) - Coltri, Mariana Bianchini Malerba (2017)
In this study, we analyze the relevance of the images in herbaria from the XVIth century, emphasizing mainly some aspects of the relation between image and text present in the books of this period. We also intend to highlight the use of images for the purpose of registration and circulation of knowledge. However, to develop this study in the field of History of Science, we chose as a case study the work A New Herball, published in 1568 by the british scholar William Turner (c.1510-1568). From this work, we present some discussions about the use of images and their relevance for the knowledge about nature at that time. We complement this work with a didactic sequence acting in the interface between the History of Science and Teaching, emphasizing science as human construction and the relevance of images in the process of communication of knowledge